Effect Of Employees’ Attitude Towards ERP Post Implementation On Support Of Top Management And Business Performance – A Study Of Critical Success Factors On Post Implementation Of ERP Systems Among It Industries In India - SHRIVASTAVA, DR. ROOPAL; SURARCHITH, DR. NAVULUR KRISHNA (The journal of contemporary issues in business and government, 2021)
The aim of current research is to examine critical success factor which is impact of employee’s attitude towards post implementation on support of top management as well as business performance. The respondents for the current study were employees of IT industries in India who are working under ERP platform. Researcher formulated two research objectives and two research hypotheses and the sample size for the current study was 187. The researcher formulated one predictor variable being employee’s attitude towards ERP post implementation and two predicted variables as support of top management and business performance. The impact between predictor variable and predicted variables were weak, positive and significant. The impact of employee’s attitude towards ERP post implementation is more on support of top management than business performance. Organizations under information technology may focus more on business performance than support of top management as one of critical successful factors in post ERP implementation.